Application of Geographic Information System in Monitoring and Detecting the COVID-19 Outbreak - Mehdi REZAEI; Abbas Ali NOURI; Gyun Seok PARK; Doo Hwan KIM (Iranian Journal of Public Health, 2020)
No Abstract